Discrete‐Time Uncertain Event‐Triggered H∞ Control for Slow Sampling Markov Jump Systems With Strictly Dissipativity - Kchaou, Mourad; Syed Ali, M.; Vigneshwar, B.; Sanober, Sumaya; Ibrahim, Tarek F.; D Alanazi, Faizah (Mathematical methods in the applied sciences, 2025)
ABSTRACT This paper investigates the H∞$$ H_{∞ } $$ control problem for discrete‐time uncertain slow sampling Markov jump systems under the event‐triggered scheme. Discrete‐time Markov jumps are controlled using an event‐triggered scheme. An event‐based strategy is addressed to reduce the data communication and improve the control efficiency. By applying a switched Lyapunov functional and linear matrix inequalities (LMIs), we derive sufficient conditions for (Q,S,R)−γ$$ \left(Q,S,R\right)-γ $$‐dissipativity of the resulting system. An event‐triggered scheme is introduced into LMIs approaches in order to solve the dissipative control problem. The control strategy is implemented by combining the disturbance output with state feedback control law in order to achieve asymptotically stable closed‐loop systems. Convex combination approach is utilized to handle slow sampling input, while parameter uncertainty and external disturbances are both included, and the robustness H∞$$ H_{∞ } $$ performance is analyzed. The developed methods are illustrated with two examples that illustrate their flexibility and applicability.